Exosomes From Packed Red Cells Induce Human Mast Cell Activation and the Production of Multiple Inflammatory Mediators - Fang, Xiaobin; Li, Jingyi; Hao, Xuechao; Zhang, Weiyi; Zhong, Jie; Zhu, Tao; Liao, Ren (Frontiers in Immunology, 2021)
Most blood transfusion-related adverse reactions involve the immunologic responses of recipients to exogenous blood components. Extracellular vesicles isolated from packed red cells can affect the recipient’s immune system. Mast cells are traditionally known as effector cells for allergic transfusion reactions. However, growing evidence supports the notion that activated mast cells might disturb host innate immunologic responses. Exosomes are a type of extracellular vesicle. To determine the effect of exosomes on mast cells, we enriched exosomes derived from volunteer plasma (EXs-nor) and packed red cells (EXs-RBCs) using ultracentrifugation and incubated them with a human mast cell line (HMC-1). We found that EXs-RBC exposure increased the expression of tryptase-1 and prostaglandin D2, the production of multiple inflammatory mediators, and the levels of Toll-like receptor-3 (TLR-3) and phospho-mitogen-activated protein kinase (MAPK) in HMC-1 cells. MAPK inhibitors (SB203580, PD98059, and SP600125) and a TLR-3/dsRNA complex inhibitor reduced the EXs-RBC-stimulated production of inflammatory mediators in HMC-1 cells, whereas the TLR-3 agonist (poly (A:U)) elevated the production of these mediators. These results indicate that EXs-RBCs activate HMC-1 cells and elicit the production of multiple inflammatory mediators, partly via the TLR-3 and MAPK pathways. Mast cells activated by EXs-RBCs exhibit complex inflammatory properties and might play a potential role in transfusion-related adverse reactions.